Development and application of a multiple-attribute decision-analysis methodology for site selection of floating offshore wind farms on the UK Continental Shelf. (October 2021) - Loughney, Sean; Wang, Jin; Bashir, Musa; Armin, Milad; Yang, Yang
Highlights: Qualitative and quantitative methodology outlined for floating wind site selection. Case study applied to Northern coast of Scotland; 45/450 sites identified. Sites are analysed and ranked against 3 main criteria and 16 basic criteria. Top 4 sites found to be adjacent, hence large site identified for floating wind. Evidential Reasoning is a viable tool in offshore wind energy site selection. Abstract: This research presents the development of a methodology for determining the most suitable floating offshore wind farm locations for the northern coast of Scotland, through the application of multi-attribute decision-analysis. A large area off the northern coast of Scotland is defined and separated into coordinate grids. The environmental, logistical and facilities factors are first analysed in order to remove sites that fall within restricted areas. Following this, data is gathered for the remaining sites in terms of a set of Logistics, Facilities & Environmental, and Met-Ocean criteria. The logistical criterion consists of such factors as, depth, distance to ports and distance to substations. The Met-ocean criterion provides a data analysis of the wind, wave, tidal and current conditions of each site between 2011 and 2016, and the Facilities & Environmental criterion analyses the proximity of the sites to such criteria as Marine Protection Areas, Special Areas of Conservation, military training areas and subsea facilities. The compiled data is then applied to a Multiple Attribute Decision Analysis (MADA) algorithm which aggregates the data for each site and produces a utility ranking in order to determine the most suitable site for floating offshore wind. Validation is conducted through benchmark testing and correlation with government survey sites.